PENGENDALIAN KUALITAS UNTUK MENURUNKAN CLAIM PRODUK COKLAT BLOK (COLLATA) MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS - Dahniar, Tedi; Sarwoko, Wanto (Jurnal Industri dan Teknologi Samawa, 2025)
PT GMK is a company in the chocolate industry, with its main product being Collata chocolate blocks. Despite being one of the leading producers, the company faces significant challenges in maintaining product quality, especially regarding color, aroma, and weight, which do not meet specifications and could potentially reduce consumer trust. This study aims to identify the root causes of product defects and offer corrective solutions using the Failure Mode and Effect Analysis (FMEA) method and Fishbone Diagram analysis. Based on data from observations and interviews with the production and quality control teams, three main defects were identified with the highest Risk Priority Numbers (RPN): color deviation (RPN 540), aroma deviation (RPN 245), and weight deviation (RPN 120). The Fishbone analysis reveals that human, machine, environment, and method factors significantly contribute to these defects. Proposed corrective actions include retraining operators to improve process understanding, periodic calibration of weighing machines, and improving production environment conditions by adding adequate ventilation. Implementing these improvements is expected to reduce defect rates and enhance the consistency of chocolate bar quality at PT GMK. Additionally, it will strengthen the company’s competitiveness in the market by ensuring higher consumer satisfaction and loyalty